Microneedles, microneedle arrays, patches, methods

Microneedles with a dual-dissolution rate composition and porous structure address mechanical strength and hydrophilicity issues, enabling effective transdermal administration and sampling through enhanced material permeability and conductivity.

JP7606202B2Active Publication Date: 2024-12-25TOHOKU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020116647
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-06
Publication Date
2024-12-25
Estimated Expiration
2040-07-06

AI Technical Summary

Technical Problem

Conventional microneedles and microneedle arrays lack sufficient mechanical strength and hydrophilicity, leading to issues such as clogging and limited substance permeability, which affect their effectiveness in transdermal medication and other applications.

Method used

The microneedles are composed of two or more materials with different dissolution rates in phosphate buffer, featuring a porous structure with slow- and fast-dissolving components, where the voids are partially or fully filled with fast-dissolving materials, enhancing mechanical strength and hydrophilicity.

Benefits of technology

The resulting microneedles exhibit improved mechanical strength and hydrophilicity, allowing for effective transdermal administration, subcutaneous tissue fluid sampling, and transcutaneous energization with sustained functionality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606202000003
    Figure 0007606202000003
  • Figure 0007606202000004
    Figure 0007606202000004
  • Figure 0007606202000005
    Figure 0007606202000005
Patent Text Reader

Abstract

To provide a microneedle and a microneedle array having excellent mechanical strength and hydrophilicity.SOLUTION: The present invention discloses: a microneedle composed of two or more materials having different dissolution rates in phosphate buffer (PBS buffer) (pH 6.8, temperature 37°C); a microneedle array having the plurality of microneedles erecting on a base material; a patch including the microneedle array and a plurality of electrodes in contact with the microneedle array; and a method that uses the microneedle, and / or the microneedle array, and / or the patch (excluding medical practice).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to microneedles, microneedle arrays, patches and methods. [Background technology]

[0002] Minimally invasive microneedles and microneedle arrays that cause no pain when inserted are effective for transdermal drug administration, collection of subcutaneous tissue fluid, sensing of biological information, and the practical application of microneedles and microneedle arrays is rapidly progressing particularly in the field of transdermal drug administration (see Non-Patent Document 1).

[0003] For transdermal drug administration using microneedles, the microneedles need to be permeable to substances, such as liquid permeability. However, in the case of metal microneedles having a hollow structure like an injection needle, problems such as clogging of the needle hole during insertion have been pointed out. Instead, attention is being focused on the use of microneedles made of hydrogels, in which the material constituting the needle body is permeable to substances (see Non-Patent Document 2), and microneedles in which the material constituting the needle body is porous (see Patent Document 1 and Non-Patent Document 3).

[0004] These microneedles having substance permeability are effective not only in the field of transdermal drug administration, but also in the field of diagnosis and treatment using transdermal electrical current (see Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-000724 A [Patent Document 2] JP 2019-107040 A [Non-patent literature]

[0006] [Non-Patent Document 1] J. Yang et al., "Recent Advances of Microneedles for Biomedical Applications: Drug Delivery and Beyond", Acta Pharmaceutica Silica B, 9 (2019) 469. [Non-Patent Document 2] RF Donnelly, et al., Journal of Pharmaceutical Science, 2014, 103, 1478-1486. [Non-Patent Document 3] L. Liu et al., "Porous Polymer Microneedles for Rapid Fluid Transport by Massively Parallel Microchannels", RSC Advances, 6 (2016) 48630. Summary of the Invention [Problem to be solved by the invention]

[0007] However, there is still room for improvement in the characteristics of the above-mentioned conventional microneedles and microneedle arrays. Therefore, the present invention aims to provide a microneedle and a microneedle array having excellent mechanical strength and hydrophilicity. The present invention also aims to provide a patch using such a microneedle and a microneedle array. The present invention also aims to provide a method for using such a microneedle and a microneedle array. [Means for solving the problem]

[0008] The gist of the present invention is as follows. The microneedle of the present invention is characterized by being composed of two or more materials having different dissolution rates in a phosphate buffer solution (PBS buffer solution) (pH 6.8, temperature 37° C.). In the microneedle of the present invention, it is preferable that the two or more materials having different dissolution rates in water include a slow-soluble material having a dissolution rate of 0.001 mass% / hour or more and 2 mass% / hour or less, and a fast-soluble material having a dissolution rate of 3 mass% / hour or more. The microneedle of the present invention preferably has a porous structure formed from one or more of the two or more materials. In the microneedle of the present invention, it is preferable that all or part of the voids in the porous structure are filled with a material other than the material that forms the porous structure. The microneedle of the present invention preferably has a porous structure formed by the slowly soluble material. In the microneedle of the present invention, it is preferable that all or a part of the voids in the porous structure is filled with a fast-dissolving material. In the microneedle of the present invention, the porosity of the porous structure of the microneedle is preferably 5% by volume to 90% by volume. In the microneedle of the present invention, the ratio of the material forming the porous structure is preferably 5% by mass to 90% by mass. In the microneedle of the present invention, the content of materials other than the material that forms the porous structure is preferably 0.001% by mass to 60% by mass. In the microneedle of the present invention, the ratio of the volume of the material other than the material that forms the porous structure to the volume of the material that forms the porous structure is preferably 0.001 vol % to 60 vol %. In the microneedle of the present invention, the air bubble ratio of the microneedle is preferably 10% by volume to 90% by volume. In the microneedle of the present invention, the slowly soluble material and / or the rapidly soluble material is preferably a biodegradable material. Here, in the microneedle of the present invention, it is preferable that the slowly soluble material is selected from the group consisting of polylactic acid-co-glycolic acid (PLGA) and mixed materials mainly composed of PLGA, β-tricalcium phosphate, calcium carbonate, polycaprolactone, polydioxanone, hydroxyapatite, polyethylene glycol, and magnesium alloys. In addition, in the microneedle of the present invention, it is preferable that the fast-dissolving material is selected from the group consisting of polyvinyl alcohol, polyallylamine, cellulose nanofiber, carboxymethylcellulose, hyaluronic acid, collagen, trehalose, PLGA-polyethylene glycol (PEG) copolymer, Pluronic F127, phospholipids, dopamine, tannic acid, silane coupling agents, and phosphonic acid derivatives. In particular, in the microneedle of the present invention, it is preferable that the slowly soluble material contains polylactic acid-co-glycolic acid (PLGA). It is preferable that when the microneedle of the present invention is immersed in Ringer's solution (25°C) for one year, the ratio of the amount of the slowly-soluble material after immersion to the amount of the slowly-soluble material before immersion (slow-soluble material residual rate) is 99 mass% or less. It is preferable that when the microneedle of the present invention is immersed in Ringer's solution (25°C) for one year, the ratio of the amount of the fast-soluble material after immersion to the amount of the fast-soluble material before immersion (fast-soluble material residual rate) is 0.1 mass% or more. It is preferable that when the microneedle of the present invention is immersed in water (pH 7, temperature 25°C) for 1 hour, the ratio of the mechanical strength at the tip of the microneedle after immersion to the mechanical strength at the tip of the microneedle before immersion is 0.1 to 97%. The microneedle array of the present invention is characterized in that a plurality of the above-mentioned microneedles of the present invention are provided upright on a substrate. In the microneedle array of the present invention, the microneedles preferably comprise a pillar-shaped body provided with small microneedles. The microneedle array of the present invention preferably comprises a plurality of the small microneedles and a plurality of the pillars. The patch of the present invention is characterized by comprising the above-mentioned microneedle array of the present invention and a plurality of electrodes provided in contact with the microneedle array. The transdermal administration method of the present invention is characterized by using the above-mentioned microneedle of the present invention, and / or the above-mentioned microneedle array of the present invention, and / or the above-mentioned patch of the present invention (however, medical procedures are excluded). The method for sampling subcutaneous tissue fluid of the present invention is characterized by using the microneedle of the present invention, and / or the microneedle array of the present invention, and / or the patch of the present invention (however, medical procedures are excluded). The transdermal electrical current method of the present invention is characterized by using the above-mentioned microneedle of the present invention, and / or the above-mentioned microneedle array of the present invention, and / or the above-mentioned patch of the present invention (however, medical procedures are excluded). Effect of the Invention

[0009] According to the present invention, it is possible to provide a microneedle and a microneedle array having excellent mechanical strength and hydrophilicity. In addition, the present invention can provide a patch using such a microneedle and a microneedle array. Furthermore, the present invention can provide a method using such a microneedle and a microneedle array. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing an example of the configuration of a microneedle of this embodiment, which has a porous structure formed of a slow-dissolving material, and is a diagram showing a microneedle of this embodiment in which all or part of the voids in the porous structure are filled with a fast-dissolving material. (A) is an example in which all of the voids in the porous structure are filled with a fast-dissolving material. (B) is an example in which part (tip part) of the voids in the porous structure is filled with a fast-dissolving material. (C) is an example in which part (tip part and side part) of the voids in the porous structure are filled with a fast-dissolving material. [Diagram 2]2A and 2B are perspective views showing an example of the microneedle array of this embodiment, where FIG. 2A is a perspective view showing an example of the microneedle array of this embodiment, and FIG. 2B is a perspective view showing another example of the microneedle array of this embodiment. [Diagram 3] FIG. 3 is a diagram for explaining an outline of the manufacturing method of Test Example 1. [Figure 4] FIG. 4 is a diagram for explaining an outline of the production method of Test Example 2. [Diagram 5] 5 is a diagram showing an example of a patch of this embodiment, where (A) is a perspective view of the example patch, (B) is a cross-sectional view showing an enlarged portion of the patch when the patch shown in (A) is used as a means for administering medicine, (C) is a cross-sectional view showing an enlarged portion of the patch when the patch shown in (A) is used as a means for collecting body fluids, and (D) is a photograph showing the example patch attached to the arm of a subject. [Figure 6] 6 is a diagram showing a configuration example of the method of this embodiment using the microneedle and microneedle array of this embodiment shown in FIG. 1. (A) is a diagram showing how a microneedle is inserted into the skin and a fast-dissolving material filled in the voids in the porous structure is administered transdermally as a drug. (B) is a diagram showing how a microneedle is inserted into the skin and administered transdermally through the porous structure, and also shows how subcutaneous tissue fluid is sampled through the porous structure. (C) is a diagram showing how a microneedle is inserted into the skin and a transdermal current is applied through the porous structure. [Figure 7] Figure 7 shows photographs of a microneedle array observed with an optical microscope in a state where PLGA was not filled with CMC during the production process of Test Example 1. (A) is an optical microscope photograph of the microneedle array after the entire mold was centrifuged. (B) is an optical microscope photograph of the microneedle array after freeze-drying. (C) is an optical microscope photograph showing an enlarged portion of (B). [Figure 8]8 shows photographs of a microneedle array in a state where PLGA was filled with CMC during the production process of Test Example 1, observed with an optical microscope. (A) is an optical microscope photograph of the microneedle array after immersion and evacuation. (B) is an optical microscope photograph of the microneedle array after air drying. (C) is an optical microscope photograph showing an enlarged portion of (B). [Figure 9] 9 is a set of photographs showing the state of measurement of the mechanical strength of the microneedle obtained in Test Example 1. (A) is an overview photograph, and (B) is an enlarged photograph. [Figure 10] FIG. 10 is a chart summarizing the results of evaluating the load / strain (N / mm) in measuring the mechanical strength of the microneedle. [Figure 11] 11 is a set of photographs showing the state of image evaluation of deformation at the tip of a microneedle in measuring the mechanical strength of the microneedle. (A) (top) is a photograph showing the state of image evaluation of deformation at the tip of a microneedle obtained in Test Example 1. (B) (bottom) is a photograph showing the state of image evaluation of deformation at the tip of a comparative microneedle (only PLGA). [Figure 12] FIG. 12 is a diagram illustrating an outline of an evaluation system for evaluating the ionic conductivity of microneedles. [Figure 13] 13 is a diagram showing the results of evaluating the ionic conductivity of the microneedles of Test Example 1. (A) is a chart showing the change over time (0 to 60 minutes) of the resistance of the microneedles of Test Example 1. The vertical axis shows resistance (kΩ), and the horizontal axis shows time (minutes). (B) is a chart showing an enlarged portion of the chart shown in (A) from 15 to 60 minutes. The vertical axis shows resistance (kΩ), and the horizontal axis shows time (minutes). [Figure 14] 14 is a chart showing the change in resistance of comparative microneedles (PLGA only) over time, with the vertical axis showing resistance (kΩ) and the horizontal axis showing time (min). [Figure 15] FIG. 15 is a chart summarizing the results of evaluating the dissolution rate of the microneedles in Test Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, microneedles and microneedle arrays according to embodiments of the present invention (hereinafter also referred to as "present embodiments") will be illustrated in detail with reference to the drawings.

[0012] (Microneedle) The microneedle of this embodiment is characterized in that it is made of two or more materials having different dissolution rates in a phosphate buffer solution (PBS buffer solution) (pH 6.8, temperature 37° C.).

[0013] FIG. 1 is a diagram showing an example of the configuration of a microneedle according to this embodiment. In FIG. 1, the dissolution rate of the material forming the skeleton of the microneedle (shown in light gray in the figure) is different from the dissolution rate of the material inside the microneedle (shown in dark gray in the figure).

[0014] In a preferred embodiment, the two or more materials having different dissolution rates in water include a slowly-soluble material having a dissolution rate of 0.001 mass % / hour or more and 2 mass % / hour or less, and a quickly-soluble material having a dissolution rate of 3 mass % / hour or more.

[0015] The dissolution rate (mass% / hour) is a value obtained by subtracting the mass of the sample after immersion for a predetermined time (one year for slow-dissolving materials, one hour for fast-dissolving materials) from the mass of the sample before immersion for a predetermined time, and then drying for one hour at 37°C, and dividing the result by the predetermined time. For example, PBS(-) from Fujifilm Wako Pure Chemical Industries, Ltd. can be used as the phosphate buffer (PBS buffer).

[0016] Regarding the dissolution rate of the slowly-soluble material, from the viewpoint of the balance between mechanical strength and hydrophilicity, the lower limit is preferably 0.002 mass% / hour or more, and even 0.01 mass% / hour or more, and the upper limit is preferably 2 mass% / hour or less, and even 1 mass% / hour or less. Regarding the dissolution rate of the fast-dissolving material, from the viewpoint of the balance between mechanical strength and hydrophilicity, the lower limit is preferably 3 mass% / hour or more, 10 mass% / hour or more, 30 mass% / hour or more, 90 mass% / hour or more, 3 mass% / min, 10 mass% / min, 30 mass% / min, 90 mass% / min, 3 mass% / sec, 10 mass% / sec, 30 mass / % / sec, or 90 mass% / sec, and the upper limit is preferably 100 mass% / sec or less, or 99 mass% / sec or less.

[0017] The microneedle of this embodiment may contain materials other than the slow-soluble material and the fast-soluble material (for example, a hydrophilizing material described below).

[0018] The microneedle of this embodiment preferably has a porous structure formed from one or more of the two or more materials. By using a porous structure as the basic skeleton, mechanical strength can be easily obtained at the time of insertion of the microneedle or for a certain period of time after insertion.

[0019] It is preferable that all or a part of the voids in the porous structure are filled with a material other than the material that forms the porous structure, where "filled" means that most of the material does not escape from the voids when the porous structure is left to stand at room temperature and pressure.

[0020] More specifically, in this embodiment, it is more preferable to have a porous structure formed by a slow-dissolving material. By using a porous structure formed from a slowly soluble material as the basic skeleton, it becomes easier to obtain mechanical strength for a longer period during or after the insertion of the microneedle.

[0021] More specifically, it is preferable that all or a part of the voids in the porous structure is filled with a fast-dissolving material.

[0022] FIG. 1 is a diagram showing an example of the configuration of a microneedle of this embodiment, which has a porous structure formed of a slow-dissolving material, and is a diagram showing a microneedle of this embodiment in which all or part of the voids in the porous structure are filled with a fast-dissolving material. (A) is an example in which all of the voids in the porous structure are filled with a fast-dissolving material. (B) is an example in which part (tip part) of the voids in the porous structure is filled with a fast-dissolving material. (C) is an example in which part (tip part and side part) of the voids in the porous structure are filled with a fast-dissolving material.

[0023] In this embodiment, the porosity of the porous structure of the microneedles is preferably 5 volume % to 90 volume %, with the lower limit being preferably 10 volume % or more, 20 volume % or more, or 30 volume % or more, and the upper limit being 80 volume % or less, 70 volume % or less, or 60 volume % or less.

[0024] The porosity (volume %) refers to the value obtained by subtracting the volume of the material forming the porous structure from the volume of the microneedle (the volume of the region defined by the outer contour) and dividing the result by the volume of the microneedle. The porosity is specifically measured by the method described in the examples.

[0025] The composition of the material of the microneedle of this embodiment will be described.

[0026] In the microneedle of this embodiment, the proportion of the material forming the porous structure is preferably 5% by mass to 90% by mass, with the lower limit being preferably 10% by mass or more, 20% by mass or more, or 30% by mass or more, and the upper limit being preferably 80% by mass or less, 70% by mass or less, or 60% by mass or less.

[0027] In the microneedle of this embodiment, the proportion of materials other than the material that forms the porous structure is preferably 0.001% by mass to 60% by mass, with the lower limit being preferably 0.005% by mass or more, or even 0.01% by mass or more, and the upper limit being preferably 50% by mass or less, or even 40% by mass or less.

[0028] More specifically, in the microneedle of this embodiment, assuming the microneedle to be 100% by mass, the content of the slowly soluble material and the rapidly soluble material is preferably 30% by mass to 99.9% by mass, with the lower limit being preferably 50% by mass or more, 70% by mass or more, or 90% by mass or more, and the upper limit being preferably 99% by mass or less, 98% by mass or less, or 95% by mass or less. The content may be 100% by mass.

[0029] More specifically, it is preferable that the content of the slow-soluble material as a material forming a porous structure is 5% by mass to 90% by mass, and the content of the fast-soluble material as a material other than the material forming a porous structure is 0.001% by mass to 60% by mass.

[0030] The microneedle of this embodiment may be subjected to hydrophilization treatment using a hydrophilizing material such as an amphiphilic polymer or a surface modifier. In such a case, in the microneedle of this embodiment, assuming the microneedle to be 100% by mass, more specifically, the content of the hydrophilizing material is preferably 0.0001% by mass to 40% by mass, with the lower limit being preferably 0.0005% by mass or more, or even 0.001% by mass or more, and the upper limit being preferably 20% by mass or less, or even 10% by mass or less.

[0031] In this embodiment, the ratio of the volume of materials other than the material that forms the porous structure to the volume of the material that forms the porous structure is preferably 0.001 volume % to 60 volume %, with the lower limit being preferably 0.005 volume % or more, or even 0.01 volume % or more, and the upper limit being preferably 50 volume % or less, or even 40 volume % or less.

[0032] In this embodiment, the air bubble ratio of the microneedles is preferably 10 volume % to 90 volume %, with the lower limit being preferably 20 volume % or more, or 30 volume % or more, and the upper limit being 85 volume % or less, or 80 volume % or less. The air bubble ratio (volume %) refers to the value obtained by subtracting the volume of the material forming the porous structure and the volume of the material other than the material forming the porous structure from the volume of the microneedle (the volume of the region defined by the outer contour) and dividing the volume by the volume of the microneedle. The air bubble ratio can be measured in accordance with the porosity, and specifically, is measured by the method described in the examples.

[0033] The material of the microneedle of this embodiment will be described in detail.

[0034] In this embodiment, from the viewpoint of environmental friendliness, the slow-dissolving material and / or the fast-dissolving material are preferably biodegradable materials, and it is more preferable that the slow-dissolving material and the fast-dissolving material are biodegradable materials.

[0035] Examples of the slowly soluble material include polylactic acid-glycolic acid copolymer (PLGA) and mixed materials mainly composed of PLGA (materials whose content is 50% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more of the mixed material), β-tricalcium phosphate, calcium carbonate, polycaprolactone, polydioxanone, hydroxyapatite, polyethylene glycol, magnesium alloys, etc., of which polylactic acid-glycolic acid copolymer (PLGA) and mixed materials mainly composed of PLGA are preferred, and polylactic acid-glycolic acid copolymer (PLGA) is more preferred. These may be used alone or in combination of two or more.

[0036] Examples of fast-dissolving materials include polyvinyl alcohol, polyallylamine, cellulose nanofibers, carboxymethylcellulose (CMC), alginic acid, hyaluronic acid, collagen, trehalose, PLGA-polyethylene glycol (PEG) copolymer, Pluronic F127, phospholipids, dopamine, tannic acid, silane coupling agents, and phosphonic acid derivatives. Carboxymethylcellulose (CMC), hyaluronic acid, collagen, polyacrylic acid, alginic acid, sucrose, starch, trehalose, and DNA are preferred, and carboxymethylcellulose (CMC) is more preferred. These may be used alone or in combination of two or more.

[0037] In this embodiment, the slowly soluble material preferably comprises polylactic-co-glycolic acid (PLGA). The content of polylactic acid-co-glycolic acid (PLGA) in the slowly soluble material is preferably 30% by mass to 99.9% by mass, with the slowly soluble material being 100% by mass. The lower limit is preferably 50% by mass or more, or even 70% by mass or more, and the upper limit is preferably 99% by mass or less, or even 98% by mass or less. The content may be 100% by mass.

[0038] Polylactic acid-glycolic acid copolymer (PLGA) may contain 90% by mass or more of polylactic acid monomer units and glycolic acid monomer units, preferably 95% by mass or more, and particularly preferably 100% by mass. In polylactic acid-glycolic acid copolymer (PLGA), the molar ratio of polylactic acid monomer units to glycolic acid monomer units is preferably 97:3 to 3:97, with the lower limit being preferably 95:5 or more, or 90:10 or more, and the upper limit being preferably 5:95 or less, or 10:90 or less. The weight average molecular weight (Mw) of polylactic acid-glycolic acid copolymer (PLGA) is preferably 1,000 to 700,000, with the lower limit being preferably 2,000 or more, 3,000 or more, 10,000 or more, 50,000 or more, or 100,000 or more, and the upper limit being preferably 500,000 or less, or 300,000 or less. The weight-average molecular weight (Mw) can be measured by gel permeation chromatography (GPC). In particular, a calibration curve is prepared from the elution time and Mw using a standard PLGA with a known Mw and an analytical gel column, and the weight-average molecular weight (Mw) of the sample PLGA can be determined using the calibration curve obtained.

[0039] Regarding the above-mentioned hydrophilic material, examples of the amphiphilic polymer include, but are not limited to, polylactic acid-co-glycolic acid (PLGA)-polyethylene glycol (PEG) copolymer, Pluronic F127 (registered trademark), phospholipids, etc., and examples of the surface modifier include, but are not limited to, dopamine, tannic acid, silane coupling agents, phosphonic acid derivatives, etc. These may be used alone or in combination of two or more.

[0040] The microneedle of this embodiment has the characteristic that its constituent materials dissolve after insertion, and therefore its properties are different before and after insertion, in other words, before and after use. These features are described in detail below.

[0041] When the microneedle of this embodiment contains a slow-soluble material as a material that forms a porous structure and a fast-soluble material as a material other than the material that forms a porous structure, when it is completely immersed in Ringer's solution (25°C) for one year, it is preferable that the ratio of the amount of slow-soluble material after immersion to the amount of slow-soluble material before immersion (slow-soluble material residual rate) is 99 mass% or less, and the upper limit is also preferably 98 mass% or less, or 95 mass% or less. The residual rate of the slowly soluble material can be increased by increasing the weight average molecular weight (Mw), decreasing the dissolution rate, or selecting a material with low solubility.

[0042] Furthermore, when the microneedle of this embodiment contains a slowly soluble material and a rapidly soluble material as described above, when it is completely immersed in Ringer's solution (25°C) for 1 hour, the ratio of the amount of rapidly soluble material after immersion to the amount of rapidly soluble material before immersion (rapidly soluble material residual rate) is preferably 0.1 mass% or more, with the lower limit being 1 mass% or more, and even 3 mass% or more being preferable. Ringer's solution is made by dissolving 4.3 g of NaCl, 0.15 g of KCl, and 0.165 g of CaCl2·2hydrate in 500 mL of water. The residual rate of the fast-dissolving material can be increased by decreasing the porosity, and can also be increased by decreasing the temperature.

[0043] In the microneedle of this embodiment, when immersed in Ringer's solution (25°C) for 1 hour, the ratio of the mechanical strength at the tip of the microneedle after immersion to the mechanical strength at the tip of the microneedle before immersion is preferably 0.1 to 97%, with the lower limit being preferably 0.5% or more, even 1% or more, and the upper limit being preferably 95% or less, even 90% or less. By lowering the ratio before immersion to after immersion, the needle can function only at the time of insertion and in the area adjacent thereto, thereby reducing invasiveness. The above ratio can be reduced by making the void ratio relatively large while making the air bubble ratio relatively small.

[0044] The mechanical strength (N) at the tip of the microneedle refers to the load (N) at which deformation occurs at the tip (displacement of 20 μm or more at the tip position) when a load is applied to a microneedle sample in the axial direction of the microneedle using a load measuring device.

[0045] (Microneedle Array) The microneedle array of this embodiment has a plurality of microneedles of this embodiment standing on a substrate. FIG. 2 is a perspective view showing an example of a microneedle array according to this embodiment.

[0046] In this embodiment, the substrate of the microneedle array and the microneedles may be made of the same material.

[0047] Hereinafter, preferred shapes of the microneedles (hereinafter also referred to as "MN") in the microneedle array (hereinafter also referred to as "MNA") will be described.

[0048] The three-dimensional shape of the microneedle is not particularly limited as long as it can be inserted into the skin, and examples of the shape include a truncated cone shape, a cone shape, a square pyramid shape, a truncated square pyramid shape, and other shapes.

[0049] FIG. 2(A) is a perspective view showing an example of the microneedle array of this embodiment. In the microneedle array of this embodiment (indicated by reference symbol 1 in FIG. 2(A)), it is preferable that the microneedles include a columnar body equipped with small microneedles (indicated by reference symbol 2 in FIG. 2(A)) (see FIG. 2(A)). Here, the three-dimensional shape of the small microneedle is not particularly limited as long as it can be inserted into the skin, but a cone shape is preferable. Also, the three-dimensional shape of the columnar body is not particularly limited, but a cylinder shape is preferable.

[0050] Suitable dimensions for the example MNA shown in FIG. 2(A) are as follows: The diameter Rp of the cylindrical support portion may be 0.2 to 1 mm, and may be 0.3 mm as described in the examples. The height Hp of the cylindrical support portion may be 0.2 to 1 mm, and may be 0.2 mm as described in the examples. The diameter Rb of the bottom circle of the cone-shaped small MN may be 20 to 500 μm, and from the viewpoints of ease of preparation, ease of piercing into the skin, and mechanical strength, it is preferably 100 to 400 μm, and may be 100 μm as described in the examples. The height H of the cone-shaped small MN may be 20 to 1000 μm, and from the viewpoint of penetrating the stratum corneum when applied to the skin and securing a sufficient contact area with the epidermis and preventing invasion of the dermis, it is preferably 30 to 600 μm, and may be 200 μm as described in the examples. When the microneedles are arranged at equal distances in the vertical and horizontal directions, the distance (pitch) P between the microneedles MN (see FIG. 2(A)) may be 500 to 3000 μm, preferably 1000 to 2000 μm, or may be 700 μm as described in the examples. The thickness t (see FIG. 2(A)) of the substrate (denoted by reference symbol 5 in FIG. 2(A)) may be 10 to 2000 μm, preferably 300 to 1000 μm, and may be 450 μm as described in the examples.

[0051] FIG. 2(B) is a perspective view showing another example of the microneedle array of this embodiment. The microneedle array of this embodiment (indicated by reference symbol 1 in FIG. 2(B)) preferably comprises a plurality of small microneedles (indicated by reference symbol 2 in FIG. 2(B)) and includes a plurality of pillars (see FIG. 2(B)).

[0052] Preferred dimensions for another example MNA shown in FIG. 2(B) are as follows: The diameter Rp' of the cylindrical support portion may be 0.2 to 1 mm. The height Hp' of the cylindrical support portion may be 0.2 to 1 mm. The diameter Rb' of the bottom circle of the cone-shaped small MN may be 20 to 500 μm. The height H' of the cone-shaped small MN may be set to 50 μm to 1000 μm. When the microneedles 2 are arranged at equal distances in the vertical and horizontal directions, the distance (pitch) Q between the microneedles MN (see FIG. 2(B)) is preferably 500 to 3000 μm, and more preferably 1000 to 2000 μm. The number of small cone-shaped MNs arranged on the support portion of the cylindrical body may be 1 to 20, and preferably 3 to 9. When the small MNs are arranged at equal distances in the vertical and horizontal directions on the circular top surface of the support portion, the distance (pitch) (not shown) between the MNs is preferably 10 to 500 μm, and more preferably 100 to 200 μm. In particular, when the number of small MNs is seven, it is preferable to place one at the center of the circular top surface of the support part and six around the center. In this case, it is preferable to place the six small MNs at equal intervals on a circumference having a radius of distance d from the center. The distance d may be 50 to 500 μm, and preferably 100 to 300 μm. The thickness t (see FIG. 3(A)) of the substrate (denoted by reference numeral 5 in FIG. 2(B)) may be 10 to 2000 μm, and preferably 300 to 1000 μm.

[0053] (Method of manufacturing microneedles and microneedle arrays) The microneedles and microneedle arrays of the present embodiment are not particularly limited and may be manufactured by a method commonly used in this technical field.

[0054] When the MNA is based on a porous body, the MNA of this embodiment may be manufactured, for example, by molding a first material (e.g., a slow-soluble material) to prepare an MNA having a porous structure made of the first material, and filling the voids of the MNA with a second material (e.g., a fast-soluble material) (see FIG. 3). Furthermore, when the MNA is based on a porous body, the MNA of this embodiment may be manufactured, for example, by premixing a material that forms a porous structure (e.g., a slow-soluble material) with a material other than the material that forms a porous structure (e.g., a fast-soluble material) and molding the premix (see FIG. 4). The molding method and filling method are not particularly limited, and a method commonly used in the art may be used.

[0055] (patch) The patch of this embodiment includes the microneedle array of this embodiment and a plurality of electrodes provided in contact with the microneedle array. Here, the number of electrodes is not particularly limited as long as it is plural, but may be two, three, four, five or more including the cathode and the anode, and is preferably two consisting of the cathode and the anode.

[0056] 5 is a diagram showing an example of a patch of this embodiment, where (A) is a perspective view of the example patch, (B) is a cross-sectional view showing an enlarged portion of the patch when the patch shown in (A) is used as a means for administering medicine, (C) is a cross-sectional view showing an enlarged portion of the patch when the patch shown in (A) is used as a means for collecting body fluids, and (D) is a photograph showing the example patch attached to the arm of a subject.

[0057] The patch of this embodiment further includes an electronically conductive member for electrically connecting the electrodes (see FIG. 5). From the viewpoint of obtaining an electroosmotic flow, the patch of this embodiment preferably includes a DC power source electrically connected to the electrodes. On the other hand, the patch of this embodiment may not include a DC power source itself, but may include a device (biorecharger) that obtains a DC current by utilizing an oxidation-reduction reaction caused by a catalyst such as an enzyme together with the microneedles. In this case, the patch generates a DC current by an oxidation-reduction reaction between an enzyme substrate contained in a body fluid obtained through the microneedles inserted into the skin or an enzyme substrate previously provided as a fuel inside the patch and an enzyme supported on the electrode, or between oxygen in the air and a catalyst supported on the electrode.

[0058] Furthermore, the patch of this embodiment may further include an ion-conductive member between the MNA and the electrode, in which case the MNA and the electrode are in indirect contact with each other. The ion-conductive member may be a drug tank containing a drug solution such as an enzyme substrate as fuel for the biocell.

[0059] The shape of the electrode in the patch of this embodiment is not particularly limited. In addition, the material of the electrode includes carbon materials such as carbon nanotubes, ketjen black, glassy carbon, graphene, fullerene, carbon fiber, carbon fabric, and carbon aerogel; conductive polymers such as polyaniline, polyacetylene, polypyrrole, poly(p-phenylene vinylene), polythiophene, and poly(p-phenylene sulfide); semiconductors such as silicone, germanium, indium tin oxide (ITO), titanium oxide, copper oxide, and silver oxide; metals such as gold, platinum, titanium, aluminum, tungsten, copper, iron, and palladium, and the like. In particular, carbon materials such as carbon fabric and carbon nanotubes are preferred from the viewpoints of flexibility and electrochemical stability.

[0060] In particular, when the patch includes a device (biocell) that obtains a direct current by utilizing an enzyme-induced redox reaction together with the microneedle, the electrodes preferably include at least one positive electrode (cathode) or negative electrode (anode) carrying an enzyme that catalyzes the redox reaction. In this case, the electrode material is preferably the above-mentioned carbon material from the viewpoint of immobilizing the enzyme on the electrode at a high density, and in particular, carbon fabric modified with carbon nanotubes is preferable. Examples of catalysts for the reduction reaction carried on the positive electrode (cathode) include bilirubin oxidase (BOD), laccase, Cu efflux oxidase (Cueo), ascorbic acid oxidase, iron phthalocyanine, etc., and in particular, bilirubin oxidase (BOD) and iron phthalocyanine are preferable from the viewpoint of increasing resistance to pH, chloride ions, etc. Examples of the enzymes that catalyze the oxidation reaction supported on the negative electrode (anode) include glucose oxidase, glucose dehydrogenase (GDH), fructose dehydrogenase (D-Fructose Dehydrogenase, FDH), alcohol oxidase, alcohol dehydrogenase, lactate oxidase, lactate dehydrogenase, etc., and glucose dehydrogenase (GDH) and fructose dehydrogenase (FDH) are particularly preferred because they can simplify the enzyme reaction system. Among these, the combinations of BOD and iron phthalocyanine with GDH and FDH are particularly preferred because they can exhibit high activity under the condition of pH 5, which is equivalent to the pH on the outer surface of the living tissue. The enzymes that catalyze the reduction reaction and the enzymes that catalyze the oxidation reaction may each be used alone or in combination of two or more.

[0061] The patch of this embodiment can be configured as a body fluid sampling device or a drug administration device. (Patch manufacturing method) The patch of the present embodiment may be manufactured by a method commonly used in the art without any particular limitation.

[0062] (method) Various methods can be provided using the microneedle, microneedle array, and patch of the present embodiment.

[0063] The microneedles, microneedle arrays, and patches of the present embodiment may be applied to humans and non-humans (e.g., pigs, cows, chickens, sheep, goats, rabbits, dogs, cats, etc.), and specifically, to human and non-human skin. More specifically, the microneedles, microneedle arrays, and patches of the present embodiment may be attached to the outer surface of the epidermis of the skin, as long as this does not constitute a medical surgical procedure such as puncture.

[0064] FIG. 6 is a diagram showing a configuration example of the method of this embodiment using the microneedle and microneedle array of this embodiment shown in FIG.

[0065] FIG. 6(A) is a diagram showing how a microneedle is inserted into the skin and a fast-dissolving material filled in the voids in the porous structure is administered transdermally as a drug.

[0066] The method of the present embodiment may be a transdermal administration method (excluding medical procedures), and such a transdermal administration method may use the microneedle of the present embodiment, and / or the microneedle array of the present embodiment, and / or the patch of the present embodiment.

[0067] The method of the present embodiment may be a method for sampling subcutaneous tissue fluid (excluding medical procedures), and such a method for sampling subcutaneous tissue fluid may use the microneedle of the present embodiment, and / or the microneedle array of the present embodiment, and / or the patch of the present embodiment.

[0068] FIG. 6(B) is a diagram showing how a microneedle is inserted into the skin and a drug is administered transdermally through a porous structure, and also shows how subcutaneous tissue fluid is sampled through the porous structure.

[0069] The method of the present embodiment may be a transdermal electrical current method (excluding medical procedures), and such a transdermal electrical current method may use the microneedle of the present embodiment, and / or the microneedle array of the present embodiment, and / or the patch of the present embodiment.

[0070] FIG. 6(C) is a diagram showing how a microneedle is inserted into the skin and a current is passed through the skin via the porous structure.

[0071] The above describes exemplary embodiments of the microneedle, microneedle array, patch, and method of the present invention with reference to the drawings. However, the microneedle, microneedle array, patch, and method of the present invention are not limited to the above examples, and appropriate modifications can be made to the above embodiments. EXAMPLES

[0072] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.

[0073] A. Reagents and Materials The following reagents and materials were used: The slow-dissolving materials used were polylactic acid / glycolic acid copolymers (PLGA) (combinations of polylactic acid:glycol (molar ratio) of 75:25 and 50:50, and weight-average molecular weights (Mw) of 20 kDa, 97 kDa, and 76-115 kDa; all manufactured by Polyscience). Fast-dissolving and hydrophilic materials include sodium carboxymethylcellulose (CMC, C5678, manufactured by Sigma Aldrich) and microfibrous cellulose (Celish FD100G, manufactured by Daicel FineChem). Polydimethylsiloxane (PDMS) (Sylgard 184, Dow Corning) as a mold material for microneedles with a porous structure. The solvent was 1,4-dioxane (D0860, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0074] B. Microneedle Array Fabrication

[0075] (Test Example 1) A cutting machine (manufactured by Modia Systems) was used to create a Teflon (registered trademark) mold (female mold) with multiple microneedle array shapes engraved into it, and then a male mold was created from polydimethylsiloxane (PDMS). This was a two-step transfer process to obtain a PDMS female mold. The dimensions of the mold (dimensions of the microneedle array) were adjusted to match the dimensions of the microneedle array described below. The shape of the microneedle array was a cone (see FIG. 2(A)). The dimensions of the mold (dimensions of the microneedle) were as follows: -Cylindrical support part diameter Rp0.3mm The height Hp of the cylindrical support is 0.2 mm - Diameter of bottom circle Rb: 100μm Height H: 200μm Distance between MNs (pitch) P: 700μm · Substrate thickness: 450μm FIG. 3 is a diagram for explaining an outline of the manufacturing method of Test Example 1. As shown in Figure 3, a solution of PLGA, a slowly soluble and biodegradable material, dissolved in 1,4-dioxane was introduced into the mold, and the entire mold was centrifuged at 3700 rpm for 10 minutes to fill the solution up to the tip of the needle. Next, the mixture was frozen at -80°C for 2 hours to obtain a porous portion made of 1,4-dioxane, and the 1,4-dioxane was then removed by sublimation using a freeze dryer. The molded PLGA microneedle array was released from the mold and completely immersed in a 2% by mass aqueous solution of carboxymethylcellulose (CMC), a fast-dissolving material, and then vacuumed to fill the entire microneedle array with the CMC aqueous solution. Finally, the microneedle array was removed from the aqueous solution and naturally dried at 25°C for at least 1 hour to obtain a biodegradable microneedle array in which PLGA was filled with CMC. The PLGA concentration in the solution was 20% by mass in 1,4-dioxane. The polylactic acid:glycol (molar ratio) was 75:25 and the weight average molecular weight (Mw) was 97 kDa.

[0076] FIG. 7 is a photograph of a microneedle array observed with an optical microscope in the production process of Test Example 1, in which PLGA was not filled with CMC. Figure 7(A) is an optical microscope image of the microneedle array after centrifuging the entire mold, showing that the mold was sufficiently filled with the PLGA solution by the centrifugal force, resulting in a sharp needle shape. Figure 7(B) is an optical microscope image of the microneedle array after freeze-drying. Figure 7(C) is an optical microscope image showing an enlarged portion of (B). These images show that the microneedles have a porous structure with a diameter of about 1 to 10 μm.

[0077] FIG. 8 is a photograph of a microneedle array in which PLGA was filled with CMC during the production process of Test Example 1, observed with an optical microscope. Figure 8(A) is an optical microscope image of the microneedle array after immersion and evacuation. It can be seen that the PLGA solution was sufficiently filled into the mold by centrifugal force, resulting in a sharp needle shape. No significant changes were observed in the optical microscope image due to the introduction of CMC. Figure 8(B) is an optical microscope photograph of the microneedle array after air drying, and Figure 8(C) is an optical microscope photograph showing an enlarged portion of (B). From these photographs, it was possible to see that the porous structure was filled with CMC. The photographs suggested that this filling did not completely fill all the voids in the porous structure, but that some of the voids had become air bubbles (or through holes in some cases).

[0078] C. Evaluation of Microneedle Arrays C-1. Evaluation of porosity The porosity of the microneedle arrays in PLGA without CMC filling was quantified by mass measurement. The microneedle array was completely immersed in water, and the mass of the microneedle array in which all voids were filled with water was measured. The same microneedle array was then dried and its mass was measured, and the difference in mass was calculated based on the density of water (1.0 g / cm 3 The void volume of the porous structure was calculated by dividing the void volume by the mass fraction (μm). Next, the mass of the dried microneedle array was calculated based on the density of PLGA (1.3 g / cm 3 The volume of the PLGA portion was calculated by dividing by Finally, the ratio (volume %) of the volume of the voids in this porous structure to the entire volume of the microneedle array was calculated.

[0079] In Test Example 1, the porosity of the microneedle array was found to be 43±5.3% by volume (N=3). This value corresponds to the porosity of a microneedle array made only of a slow-soluble biodegradable material (PLGA) after a fast-soluble biodegradable material (CMC) is completely dissolved when it is filled. It is believed that the porosity increases over time as the PLGA is further decomposed in the body.

[0080] In addition, in Test Example 1, it was separately confirmed from an electron microscope image that a porous structure was present in the microneedle array in which PLGA was not filled with CMC (not shown).

[0081] C-2. Mechanical strength evaluation Biodegradable microneedles need to have sufficient mechanical strength to be inserted into the skin, so we measured the mechanical strength of the microneedles. Here, mechanical strength is the strength at the yield point in load / strain (N / mm) measurements. The yield point is the force at which the material can no longer withstand the load and is deformed. The measurement procedure involved placing the needle tips of the microneedle array vertically facing upwards and using a force gauge (Imada, product name: ZTA-5N) to press a surface horizontally against the tip to evaluate the load / strain (N / mm) and also evaluating the deformation of the tip using images. 9 is a set of photographs showing the state of measurement of the mechanical strength of the microneedle obtained in Test Example 1. (A) is an overview photograph, and (B) is an enlarged photograph.

[0082] The microneedles of Test Example 1, in which carboxymethylcellulose (CMC) was filled into the porous portion of the microneedle as a fast-dissolving, biodegradable material, exhibited high load / strain. Previous research has estimated that the force required to insert a microneedle into the skin is at least 0.06 N per needle, so the 36 needles in the microneedle array of Test Example 1 must be able to withstand being pushed with a force of approximately 2.2 N. The microneedle array of Test Example 1 is considered to meet the mechanical strength standard (see Figure 10). FIG. 10 is a chart summarizing the results of evaluating the load / strain (N / mm) in measuring the mechanical strength of the microneedle.

[0083] In addition, the deformation of the needle tip when the force required to insert the microneedle into the skin (0.06 N per needle) was applied to the needle using a force gauge was evaluated by image analysis (see FIG. 11). No deformation was observed in the microneedle of Test Example 1 filled with CMC. As described below, in comparison with the microneedle made of PLGA alone, which cannot withstand the force of skin insertion, it was found that filling with CMC increases the mechanical strength, making it possible to construct a biodegradable microneedle that can be inserted into the skin. Fig. 11 is a photograph showing the state of image evaluation of deformation of the tip of the microneedle in measuring the mechanical strength of the microneedle. Fig. 11(A) (top) is a photograph showing the state of image evaluation of deformation of the tip of the microneedle obtained in Test Example 1.

[0084] Here, an MNA to be compared with the MNA of Test Example 1 was also produced, and mechanical strength was measured in the same manner as in Test Example 1.

[0085] First, microneedles were fabricated using PLGA, a slow-soluble, biodegradable material with Mw = 97,000, and with molar ratios of the constituent polylactic acid (PLA) monomer units and polyglycolic acid (PGA) monomer units of 75:25 (porosity 43% by volume) and 50:50 (porosity not measured), and the mechanical strength was measured without filling it with the fast-soluble, biodegradable material. As a result, it was confirmed that the slow-soluble, biodegradable material alone did not have sufficient mechanical strength (see Figure 10). In the case of a needle made only of PLGA (molar ratio of monomer units = 75:25), it was confirmed that the tip was crushed by about 60 μm after force was applied (see Figure 11 (B)). Figure 11 is a photograph showing the state of image evaluation of deformation at the tip of a microneedle in measuring the mechanical strength of the microneedle. Figure 11(B) (lower row) is a photograph showing the state of image evaluation of deformation at the tip of a comparative microneedle (only PLGA).

[0086] C-3. Evaluation of ionic conductivity To evaluate whether the air bubbles in the microneedles penetrated from the needle tip to underneath the substrate, the ionic conductivity (electrical resistivity) of the microneedles was measured (see Figure 12). FIG. 12 is a diagram illustrating an outline of an evaluation system for evaluating the ionic conductivity of microneedles. For the PLGA, a microneedle was inserted into an agarose gel (mock skin model) filled with Ringer's solution, a carbon electrode was placed on top and connected to an AC impedance measuring device, and the other electrode was placed on the agarose gel (see Figure 12). Ringer's solution was dripped onto the top of the electrode to prevent the microneedle from drying out, and the ionic conductivity was maintained sufficiently. In particular, since the microneedle not filled with CMC showed hydrophobicity, for the convenience of measurement, it was immersed in Ringer's solution in advance and the electrolyte solution was filled into the pores by vacuuming. Since the high frequency region of impedance roughly coincides with the DC resistance component of the system, the resistance of the system was measured by measuring the impedance at 100 kHz. The resistance of the microneedle was calculated from the resistance measurement results by subtracting the resistance of elements of the system other than the microneedle, such as the gel and electrodes, which had been measured in advance, and the ionic conductivity of the microneedle was evaluated.

[0087] After the microneedle of Test Example 1 filled with CMC was inserted into the gel, the electrolyte solution was gradually supplied to the inside from the Ringer's solution at the top of the needle and the gel at the bottom, and the top and bottom were completely conductive, resulting in a low resistance value (up to 7 kΩ) (see Figure 13(A)). When the resistance value was monitored for 60 minutes, it was confirmed that the resistance value gradually decreased (to 5.6 kΩ) (see Figure 13(B)). FIG. 13 is a diagram showing the results of evaluating the ionic conductivity of the microneedles of Test Example 1. 13(A) is a chart showing the change over time (0 to 60 minutes) of the resistance of the microneedle in Test Example 1. The vertical axis shows resistance (kΩ) and the horizontal axis shows time (minutes). 13B is an enlarged chart showing the 15 to 60 minute portion of the chart shown in (A), with the vertical axis showing resistance (kΩ) and the horizontal axis showing time (minutes).

[0088] From this, it can be assumed that microneedles filled with CMC are highly hydrophilic and therefore do not dry easily, so that the resistance value does not increase. Also, as the CMC dissolves, the size of the pores gradually increases, and instead the resistance value gradually decreases. Considering that the resistance of the dermis of the skin is approximately 10 kΩ, this kΩ-level resistance is negligible when passing electricity through the skin, and it was found that by filling it with CMC, it is possible to construct a biodegradable microneedle that can stably maintain high ionic conductivity for a long period of time.

[0089] The microneedle (porosity 43% by volume) made of only PLGA and not filled with CMC, which was used for comparison in Test Example 1, had been filled with electrolyte solution beforehand by vacuuming, and therefore showed a low resistance value (high ionic conductivity) of 1 kΩ immediately after insertion into the gel. However, it was confirmed that the resistance value gradually increased within a few minutes (see Figure 14). 14 is a chart showing the change in resistance of comparative microneedles (PLGA only) over time, with the vertical axis showing resistance (kΩ) and the horizontal axis showing time (min). Furthermore, the resistance of a microneedle made of only PLGA and not filled with CMC, which was not subjected to vacuum drawing, was as high as 400 kΩ or more (not shown). From this, it is considered that with only hydrophobic PLGA microneedles, air gradually penetrates into the internal pores of the needles and dries out, causing a loss of ionic conductivity over time.

[0090] C-4. Evaluation of dissolution rate When the microneedle of Test Example 1 was inserted into an agarose gel (3 g of agarose added to 100 mL of Ringer's solution and solidified), which serves as a simulated skin model, it was found that CMC, a rapidly soluble and biodegradable material, was dissolved, and the dissolution rate was evaluated. The masses of each of the following microneedles were measured and compared: a microneedle containing only PLGA before filling with CMC, a microneedle filled with CMC, and a microneedle filled with CMC that was inserted into an agarose gel and left to stand for 1 hour with Ringer's solution dripped on top to elute the CMC (see Figure 15). FIG. 15 is a chart summarizing the results of evaluating the dissolution rate of the microneedles in Test Example 1. As a result, when the amount before filling (38.3 mg) was taken as 100 mass%, the amount after filling increased by 17 mass% (total 44.7 mg), and after dissolution it decreased by 12 mass% from that amount (total 40.4 mg). Therefore, it was found that the amount of CMC itself dissolved at a rate of about 4.3 mg / h. In addition, since the amount dissolved after one hour was 5 mass% more than the original weight, it is believed that a small amount of undissolved CMC remains in the pores. It is suggested that this small amount of remaining CMC maintains high hydrophilicity and achieves high ionic conductivity.

[0091] Regarding the microneedle array of Test Example 1, details of the conditions and results are shown in Table 1.

[0092] (Test Example 2) A cutting machine (manufactured by Modia Systems) was used to create a Teflon (registered trademark) mold (female mold) with multiple microneedle array shapes engraved into it, and then a male mold was created from polydimethylsiloxane (PDMS). This was a two-step transfer process to obtain a PDMS female mold. FIG. 4 is a diagram for explaining an outline of the production method of Test Example 2. As shown in Figure 4, a solution of PLGA, a slow-soluble, biodegradable material, and carboxymethylcellulose (CMC), a fast-soluble material, dissolved in 1,4-dioxane was introduced into the mold, and the entire mold was centrifuged at 3,700 rpm for 10 minutes to fill the solution up to the tip of the needle. The mixture was then frozen at -80°C for 2 hours, and 1,4-dioxane was removed by sublimation using a freeze dryer. The molded PLGA microneedle arrays were released from the mold to obtain biodegradable microneedles filled with CMC.

[0093] The microneedle array of Test Example 2 was also evaluated in the same manner as Test Example 1.

[0094] Regarding the microneedle array of Test Example 2, details of the conditions and results are shown in Table 1.

[0095] [Table 1]

[0096] (Test Examples 3A to 3I) Since the hardness of PLGA, a slowly soluble, biodegradable material, changes depending on the concentration and molecular weight used, we investigated the effects of using concentrations of 10, 20, and 30 mass% in combination with weight-average molecular weights (Mw) of 20, 90, and 76-115 kDa (see Table 2). It was thought that the higher the concentration of PLGA used and the larger the molecular weight, the higher the mechanical strength of the microneedles obtained, making them more suitable for insertion into the skin. However, problems with production, such as foaming or separation during the freeze-drying process, occurred when the concentration was 30% by mass or when the molecular weight was 76 to 115 kDa, when the concentration was higher. Test Examples 3A to 3I revealed that a usage concentration of 20 mass % and a weight average molecular weight (Mw) of 97 kDa were close to the optimum values. Test Example 3E was the same as Test Example 1.

[0097] [Table 2] [Industrial Applicability]

[0098] According to the present invention, it is possible to provide a microneedle and a microneedle array having excellent mechanical strength and hydrophilicity. In addition, the present invention can provide a patch using such a microneedle and a microneedle array. Furthermore, the present invention can provide a method using such a microneedle and a microneedle array.

Claims

1. The material is composed of two or more materials having different dissolution rates in a phosphate buffer solution (PBS buffer solution) (pH 6.8, temperature 37° C.), The two or more materials having different dissolution rates include a slow-dissolving material having a dissolution rate of 0.001 mass% / hour or more and 2 mass% / hour or less, and a fast-dissolving material having a dissolution rate of 3 mass% / hour or more, The entire microneedle has a porous structure formed of one or more of the two or more materials, the porous structure is formed by the slow-dissolving material; All of the voids in the porous structure are filled with the fast-dissolving material. Microneedle.

2. The microneedle according to claim 1 , wherein the porosity of the porous structure of the microneedle is 5% by volume to 90% by volume.

3. The microneedle according to claim 1 or 2, wherein the ratio of the material forming the porous structure is 5% by mass to 90% by mass.

4. The microneedle according to any one of claims 1 to 3, wherein the ratio of materials other than the material that forms the porous structure is 0.001% by mass to 60% by mass.

5. The microneedle according to any one of claims 1 to 4, wherein the ratio of the volume of the material other than the material that forms the porous structure to the volume of the material that forms the porous structure is 0.001 vol% to 60 vol%.

6. The microneedle according to any one of claims 1 to 5, wherein the microneedle has a void content of 10% by volume to 90% by volume.

7. The microneedle according to any one of claims 1 to 6, wherein the slowly soluble material and / or the quickly soluble material is a biodegradable material.

8. The microneedle according to any one of claims 1 to 7, wherein the slowly soluble material is at least one selected from the group consisting of polylactic acid-glycolic acid copolymer (PLGA) and a mixed material mainly composed of PLGA, β-tricalcium phosphate, calcium carbonate, polycaprolactone, polydioxanone, hydroxyapatite, polyethylene glycol, and magnesium alloy.

9. The microneedle according to any one of claims 1 to 8, wherein the fast-dissolving material is at least one selected from the group consisting of polyvinyl alcohol, polyallylamine, cellulose nanofiber, carboxymethylcellulose, hyaluronic acid, collagen, trehalose, PLGA-polyethylene glycol (PEG) copolymer, Pluronic F127, phospholipids, dopamine, tannic acid, silane coupling agents, and phosphonic acid derivatives.

10. The microneedle according to any one of claims 1 to 9, wherein the slowly soluble material comprises polylactic acid-co-glycolic acid (PLGA).

11. The microneedle according to any one of claims 1 to 10, wherein when immersed in Ringer's solution (25°C) for one year, the ratio of the amount of the slowly soluble material after immersion to the amount of the slowly soluble material before immersion (slowly soluble material residual rate) is 99 mass% or less.

12. The microneedle according to any one of claims 1 to 11, wherein when immersed in Ringer's solution (25°C) for one year, the ratio of the amount of the fast-soluble material after immersion to the amount of the fast-soluble material before immersion (fast-soluble material residual rate) is 0.1 mass% or more.

13. The microneedle according to any one of claims 1 to 12, wherein when immersed in water (pH 7, temperature 25°C) for 1 hour, the ratio of the mechanical strength at the tip of the microneedle after immersion to the mechanical strength at the tip of the microneedle before immersion is 0.1 to 97%.

14. A microneedle array comprising a plurality of microneedles according to any one of claims 1 to 13 arranged upright on a substrate.

15. The microneedle array of claim 14 , wherein the microneedles comprise a post with smaller microneedles.

16. The microneedle array according to claim 15 , comprising a plurality of the small microneedles and a plurality of the pillars.

17. A patch comprising the microneedle array according to any one of claims 14 to 16, and a plurality of electrodes provided in contact with the microneedle array.

18. A transdermal drug administration method using the microneedle according to any one of claims 1 to 13, and / or the microneedle array according to any one of claims 14 to 16, and / or the patch according to claim 17 (however, excluding said transdermal drug administration method for humans).

19. A method for sampling subcutaneous tissue fluid using a microneedle according to any one of claims 1 to 13, and / or a microneedle array according to any one of claims 14 to 16, and / or a patch according to claim 17 (excluding methods for sampling subcutaneous tissue fluid in humans).

20. A method for applying transdermal current using the microneedle according to any one of claims 1 to 13, and / or the microneedle array according to any one of claims 14 to 16, and / or the patch according to claim 17 (however, excluding said method for applying transdermal current to humans).

Citation Information

Patent Citations

  • Microneedle and microneedle patch

    JP2016087474A

  • Microarrays and methods of use for delivering therapeutic agents

    JP2016511014A

  • Micro needle and micro array and method for producing the same

    JP2017000724A

  • Method for evaluating moisture amount of target region of living body

    JP2019107040A

  • method

    US20130310665A1